Improving Learning Outcomes Of Economic Role Material Grade 5 Mi Miftahul Falah Using The Role Play Method - Reiza Dwi Fatmawati; Depict Pristine Adi; Novita Nurul Islami (SOLIDARITY: Journal of Social Studies, 2022)
The selection of learning methods, strategies, and media in teaching and learning activities is essential to produce maximum learning results. In social studies learning, many teachers still use the lecture method, which is no longer a favorite method for students because it seems boring, causing laziness in learning and significantly affecting student learning outcomes. Therefore, this study aims to determine the improvement of student learning outcomes if they use the role-play method in class 5 economic role material. The research method used is a type of classroom action research with descriptive analysis. The technique used for calculation is the sampling technique. The result of using the role-play method in class 5 economic role material is to increase the interest in learning students so that all students are enthusiastic about learning activities on the economic role material and have a good impact on their learning outcomes